(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Primo quadro: magazzino normativo – 2. - Secondo quadro: analisi storico-giuridica – 3. Terzo quadro: il futuro. State and religious organisations. The Politics of the sources of law ABSTRACT: The paper intends to verify if religious freedom in the Italian legal system is undergoing a crisis. In particular, is the concept of religious freedom of the Constituent Assembly still good? Is it necessary to reform the regulation of religious freedom? Similar questions are posed with regard to the current relationship between State and religions.